Perception and Experience of Transformative Learning and Faculty Authenticity among North American Professors of Christian Education (NAPCE) - Kang, Hokyung Paul (Christian education journal, 2013)
Perception and experience of transformative learning and faculty authenticity among Christian education professors in North America were explored in this qualitative research. Through convenient purposeful sampling, 19 professors from North American Professors of Christian Education were recruited for this study and, ultimately, 16 professors participated in the whole research process. The findings from the research study consist of Christian professors’ experience and perception of transformative learning and faculty authenticity, and through the qualitative research analysis three components to “pedagogy of authenticity” were derived, namely (a) integrity; (b) facilitating disorientation; and (c) relational teaching.